Contribution of green propolis to the antioxidant, physical, and sensory properties of fruity jelly candies made with sugars or fructans - Cedeño-Pinos, Cristina; Marcucci, María Cristina [UNESP]; Bañón, Sancho (MDPI, 2021)
Enrichment with phenolic compounds is proposed as a strategy to obtain more stable and healthier candy products. A green propolis ethanolic dry extract (PEE) from Braccharis dracunculifolia (Brazilian Alecrim-do Campo) was assessed as an antioxidant in jelly candies. Three levels (0, 0.01, and 0.02% w/w) of PEE were tested in jelly candies alternatively made with two carbohydrate bases (sugars or fructans) and three fruity dyes and flavours (menthe, orange, or strawberry). Propolis polyphenol content (identified by HPLC-MS and quantified by HPLC-DAD/UV-Vis), antioxidant capacity (total phenolics and radical scavenging activity), physical properties (moisture, pH, CIELab colour, and texture profile analysis), and flavour were studied in candies. PEE was rich in polyphenols (>8.7%), including several prenylated p-coumaric, caffeoylquinic and diterpenic acids, and flavonoids, with Artepillin-C (3.4%) as the main bioactive compound. The incorporation of PEE into the hot liquor at 80◦ C for 5 min before moulding allowed a good retention of propolis polyphenols in the final product (recovery percentages of up to 97.4% for Artepillin-C). Jelly candies made with sugars or dietetic fructans have poor antioxidant properties, which depend on the dyes and flavours used. Using PEE (at 0.02%) strongly improved the antioxidant capacity (relative increases of up to 465%) of candies without altering the pH, colour, or texture, although off-flavour may appear. Propolis, due to its good antioxidant properties, has potential for use as a functional ingredient in jelly candies.
Keywords: Antioxidants; Artepillin-C; Functional candy; Polyphenols; Propolis